Strategy for strengthening and improving the organizational culture of a Public Hospital, Huánuco- 2018 - Lozano-Valdivia, Domitila (2020)
The objective was to demonstrate the effect of the improvement strategy in strengthening the organizational culture of the nursing staff of a Public Hospital of Huánuco, 2018. Methods, the study had a quantitative, prospective, analytical and longitudinal approach, with a design quasi-experimental pre and post-test. The sample was non-probabilistic with 32 nursing personnel, to whom, after informed consent and according to ethical considerations, the improvement strategy, the organizational culture scale and the survey of general-labor characteristics, previously validated and reliable, were applied. The hypotheses were tested using the Wilcoxon test for p ≤ 0.05. Results, it was evidenced that the workers of the Nursing Department of the study Hospital perceived during the pretest that the organizational culture was of an unfavorable level in the dimensions of responsibility and commitment of the staff, employee trust, trust in the institution, job satisfaction, effective communication, planning and organization, consistent vision, teamwork and service improvement. After the improvement intervention, the perception changed to the favorable level. In general, during the pretest, 62.5% (20) perceived the level of organizational culture as unfavorable; in the posttest, it was at the favorable level at 78.1% (25). The moments of the study were contrasted, obtaining significant differences in the dimensions of the organizational culture addressed. Conclusions, the improvement strategy strengthens the organizational culture of the Nursing Department, with significant differences between the pre and post-test moments (p ≤ 0.05).